Information Communication Technology (ICT) and Women Empowerment for Rural Area - Susri Adeni (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
Women at rural area should be empowered in order to help family income. In some cases, they have a productive activity to help in increasing the family income; such as having a small home industry, etc. Therefore, in supporting their economic activity, media or Information Communication Technology (ICT) is not significantly becoming a point to raise the family income or to improve the quality of society development. While in some countries, ICT is part of poverty reduction program, could help in increasing the family economy and also is used by women for their productive activities. Thus, it is also needed the women’s role, while so far, it is not calculated in. This paper is to explore about how media ICT could be part of women empowerment in helping to improve their family income especially for rural area. The result shown that in some developing countries, ICT has benefit for women in improving the family income.